PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID “CHEMBIRD” PADA MATERI KIMIA KELAS XI DI SMAN 17 MAKASSAR - Rusdi, Hikmah; -, Sudding; Yunus, Muhammad (Jurnal Ilmiah Ecosystem, 2016)
This study aims to determine the quality of android based learning media "ChemBird" on chemical material in class XI SMAN 17 Makassar. Android-based instructional media development "ChemBird" based on the key steps in the development of learning model 4-D Thiagarajan. The results of analysis of media-based learning keterlaksanaan android "ChemBird" at high category with an average value of 3.32 and meet practical criteria. The level of success in field trials showed that mastery learning IPA3 class XI student of SMAN 17 Makassar is 83.33%. The activities and student responses, as well as the ability to manage learning teacher at the high category meets the criteria of effectiveness. Based on the criteria used to assess the media-based learning android "ChemBird" is valid criteria, practical, and effective